(untitled) (Bangladesh Journal of Plastic Surgery, 2014)
Background: Scalp reconstruction following high voltage electric burn can be challenging. A useful Reconstructive algorithm is lacking. The purpose of this study was to evaluate our experience and to identify an appropriate reconstructive strategy. Methodology: This was a prospective observational study, conducted in the Burn unit of Dhaka Medical College Hospital & Department of Burn & Plastic Surgery,Sir Salimullah Medical College & Mitford Hospital over a period of five years. Reconstructive procedures, independent factors and outcomes were evaluated. A total of 7 procedures were performed in 30 patients. Techniques for reconstruction included skin grafting, outer table drilling & skin grafting, Bipedicle flap, Single rotation flap, Double opposing rotation flap, Transposition flap, Tissue expansion & primary closure. Conclusion: Important tenets for successful management of scalp defects are durable coverage, adequate debridement, preservation of blood supply, and proper wound drainage. Local scalp flaps with skin grafts remain the mainstay of reconstruction in most instances. DOI: http://dx.doi.org/10.3329/bdjps.v3i2.18251 Bangladesh Journal of Plastic Surgery July 2012, 3(2): 49-52